An examination of the health information seeking experiences of women in rural Ontario, Canada - C.N. Wathen; R.M. Harris (Information Research: An International Electronic Journal)
Introduction. Women are active information seekers, particularly in the context of managing health for themselves and their families. Rural living may present particular challenges and opportunities for women in their health information seeking. Method. Forty women living in a rural part of Ontario, Canada were interviewed using a semi-structured interview guide. They were asked about their health information seeking for both chronic and acute concerns. Analysis. Interview transcripts were organized using NVivo software (version 6) and analysed using a coding scheme iteratively developed by both authors. Results. Emerging themes included: the context of rural living, information and health literacy, the role of unanticipated information intermediaries in the search process, and the mis-match between assumptions made by 'the system' about sources of information, and women's lived realities. Conclusion. . There are unique challenges and enablers to health information seeking for women living in rural areas, including the role of formal, informal and ICT-based information intermediaries, the availability to women of required literacies for health information seeking and uptake. Research findings such as those presented in this paper can assist in better understanding both the contexts of information seeking, as well as the preferences and behaviour of those with information needs.